Upaya Peningkatan Hasil Belajar Siswa dengan Menggunakan Alat Peraga IPA Kelas IV SD Inpres Sopi Kecamatan Morotai Jaya - Amrin Sibua; Fiktor Mangembulude (Peneliti.net, 2020)
This study aims to determine whether there is an increase in learning outcomes using science teaching aids in grade IV SD Inpres Sopi, Morotai Jaya District, Morotai Island Regency. The subjects in this study were 19 grade IV students of SD Inpres Sopi, Morotai Jaya District, consisting of 9 female students and 10 male students. The teaching aids used in this study were the science teaching aids using Torso media. The type of research used in this research is classroom action research (PTK) with the stages of the research including: 1) planning, 2) implementation, 3) observation, 4) reflection. This research lasted for two cycles consisting of cycle I and cycle II. Data collection techniques used in this study include: 1) Observation, 2) Interviews, and 3) Tests. While the instruments used in this study were lesson plans, observation sheets, and formative tests. The results of this study indicate that there is an increase in learning outcomes in each cycle. This increase was in the pre-cycle students who completed the KKM 70 as many as 3 students or 15.78%. In the first cycle, the completeness percentage of 3 students who scored above the KKM 70 before the action was achieved to 6 students or 31.57%, an increase of 15.79% from the pre-cycle. Whereas in cycle II the percentage of learning completeness was achieved from 13 students who scored above the KKM 70 in cycle II to 17 students or 89.45%, an increase of 21.05% from cycle I. Thus it can be concluded that there is an increase in student learning outcomes when using Natural science props (torso) for fourth grade students of SD Inpres Sopi, Morotai Jaya District.